The prediction of student wellbeing and flourishing from university learning experiences - Zhao, Yue; Hua, Yunqing (Frontiers in Psychology, 2025)
Student wellbeing and flourishing are becoming increasingly essential in the evolving landscape of higher education. The current study explores the relationship between university students’ learning experiences and their hedonic, eudaimonic, and social wellbeing. Employing structural equation modelling and regression analyses, the study involves a total of 5,505 undergraduate students from a Hong Kong university, spanning junior to senior years and a wide range of academic disciplines. Findings reveal that students’ hedonic, eudaimonic, and social wellbeing are significantly predicted by their learning experiences. Notably, internal factors of students’ learning experiences including cognitive, social, and value developments demonstrate a stronger prediction, while external factors of students’ learning experiences like clear goals and standards, good teaching, feedback, and assessment also significantly contribute to students’ wellbeing. The study extends the current literature and offer new insights into the wellbeing benefits of student learning experiences and underscores the need for holistic strategies and tailored approaches to nurture student flourishing in higher education.